Dermatoscopia : avaliação dos padrões isolados e combinados na onicomicose por dermatófitos - Busatto, Shimena Guisso Cabral (2018)
Introduction: Dermoscopy is a method used in the clinical diagnosis of nail melanocytic lesions, and over the years it has also been used to evaluate inflammatory, immunological and infectious diseases of the nail, such as fungal infections. Dermoscopy is a useful tool in the diagnosis of onychomycosis, allowing a comprehensive analysis of the nail apparatus, which is a low cost exam and easy perform. However, diagnosis of onychomycosis is made through clinical examination and complemented by mycological exams (DME and culture), being that histology is recommended in cases of negative mycological exams. Objectives: The aim of this study is to evaluate the dermatoscopic patterns in cases of dermatophytic onychomycosis. Patients and methods: Eighty patients with clinical suspicion of onychomycosis on the first toe were evaluated, in which dermoscopic examination was performed. The technique used to identify fungi was direct mycological examination. Results: DME was positive for dermatophyte filamentous fungi in 56 patients (70%) and negative in 24 (30%). Patients who presented nail abnormalities for a period of more than five years were more prone to the diagnosis of onychomycosis (p = 0.001). The time of nail changes in patients with onychomycosis was seven and a half years, and of three years for patients without this diagnosis, demonstrating the chronic aspect of this infection. The dermatoscopic patterns found as dermatophytic onychomycosis predictors were: "cut edge" pattern (p = 0.003), longitudinal striae (p = 0.019), subungual "ruin" hyperkeratosis (p = 0.001), and yellow cromonychia (p = 0.002). Sensitivity (S) and specificity (E) of isolated dermoscopic findings were respectively: (64.3%, 54.2%) for the "trimmed edge" pattern, (73.2%, 54.2%) for longitudinal striae pattern, (85.7%, 50%) for subungual "ruin" hyperkeratosis and (78.6%; 58.3%) for yellow cromonychia. When the patterns were combined, sensitivity and specificity were: (58.9%, 70.8%) for cut edge and longitudinal striae, (62.5%, 66.7%) for longitudinal striae and subungual "ruin" hyperkeratosis, (51.8%, 75%) for the combination of cut edge, longitudinal striae and subungual "ruin" hyperkeratosis and finally, (67.9%; 83.3%) for subungual "ruin" hyperkeratosis and yellow cromonychia. Conclusions: The dermatoscopic patterns found were: "trimmed edge" pattern, longitudinal striae, yellow cromonychia and subungual "ruin" hyperkeratosis. The sensitivity of these patterns in patients with positive DME was low, except for the subungual "ruin" hyperkeratosis, which presented a sensitivity of 85.7%. When the dermatoscopic patterns were evaluated in a combination way, there was an increase in the specificity for the diagnosis of dermatophytic onychomycosis in all combinations when compared with the patterns evaluated in isolation. The association of subungual "ruin" hyperkeratosis with yellow cromonychia was the most specific (83.3%), demonstrating an increased specificity in the diagnosis of fungal nail infection when two or more dermatoscopic predicting onychomycosis findings are present at the examination.